SENYAWA FLAVANON DARI TUMBUHAN - Suyatno, ; Nurul Hidajati, ; Mahanani Tri Asri, ; Rizka Ayu Hamida, (Matematika dan Sains, 2010)
A flavanone namely 5-hydroxy-7-methoxy flavanone (pinostrobin) had been isolated from dichloromethane extract of the leaves of the Pteriss vittata. It was gained as a pale yellow needles, m.p. 96-97 oC. The molecular structure of isolate was identified by spectroscopic methods, including UV, IR, and EIMS.A flavanone namely 5-hydroxy-7-methoxy flavanone (pinostrobin) had been isolated from dichloromethane extract of the leaves of the Pteriss vittata. It was gained as a pale yellow needles, m.p. 96-97 oC. The molecular structure of isolate was identified by spectroscopic methods, including UV, IR, and EIMS.